Unconventional myosin ID is expressed in myelinating oligodendrocytes. Issue 10 (5th June 2014) - Yamazaki, Reiji; Ishibashi, Tomoko; Baba, Hiroko; Yamaguchi, Yoshihide
<x xml:space="preserve">Abstract</x> Myelin is a dynamic multilamellar structure that ensheathes axons and is crucial for normal neuronal function. In the central nervous system (CNS), myelin is produced by oligodendrocytes that wrap many layers of plasma membrane around axons. The dynamic membrane trafficking system, which relies on motor proteins, is required for myelin formation and maintenance. Previously, we found that myosin ID (Myo1d), a class I myosin, is enriched in the rat CNS myelin fraction. Myo1d is an unconventional myosin and has been shown to be involved in membrane trafficking in the recycling pathway in an epithelial cell line. Western blotting revealed that Myo1d expression begins early in myelinogenesis and continues to increase into adulthood. The localization of Myo1d in CNS myelin has not been reported, and the function of Myo1d in vivo remains unknown. To demonstrate the expression of Myo1d in CNS myelin and to begin to explore the function of Myo1d in myelination, we produced a new antibody against Myo1d that has a high titer and specificity for rat Myo1d. By using this antibody, we demonstrated that Myo1d is expressed in rat CNS myelin and is especially abundant in abaxonal and adaxonal regions (the outer and inner cytoplasm‐containing loops, respectively), but that expression is low in peripheral nervous system myelin. In culture, Myo1d was expressed in mature rat oligodendrocytes. Furthermore, an increase in expression of Myo1d during maturation of CNS white matter (cerebellum and corpus callosum) was demonstrated by histological analysis. These results suggest that Myo1d may be involved in the formation and/or maintenance of CNS myelin. © 2014 Wiley Periodicals, Inc.